2021
DOI: 10.1111/odi.13792
|View full text |Cite
|
Sign up to set email alerts
|

Effects of advanced glycation end products on dental pulp calcification

Abstract: Objective The main aim of this study was to elucidate the effects of advanced glycation end products (AGEs) on the calcification of cultured rat dental pulp cells (RDPCs) and to investigate the crystallisation ability of glycated collagen. Materials and Methods AGEs were prepared via non‐enzymatic glycation of a dish coated with type I collagen using dl‐glyceraldehyde. To investigate the effects of AGEs on RDPCs, we performed WST‐1 and lactate dehydrogenase assays; alkaline phosphatase, Alizarin Red S and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 25 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…From these records, 25 were excluded by reasons available in Figure 1 and Supporting Information File 2. Finally, 21 studies met the inclusion criteria and were included for qualitative analysis (Al‐Anesi et al, 2021; Catanzaro et al, 2006; Cintra et al, 2017; Claudino et al, 2015; Cohen et al, 1963; Delle Monache et al, 2021; Ferreira et al, 2018; Garber et al, 2009; Glickman & Shklar, 1954; Ilić et al, 2012; Inagaki et al, 2010; Lee et al, 2016; Leite et al, 2008; Leite et al, 2010; Madani et al, 2014; Milosavljević et al, 2018; Müller et al, 2015; Nakajima et al, 2014; Santamaria‐Jr et al, 2021; Sugiyama et al, 2021; Uzunoglu‐Ozyurek et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From these records, 25 were excluded by reasons available in Figure 1 and Supporting Information File 2. Finally, 21 studies met the inclusion criteria and were included for qualitative analysis (Al‐Anesi et al, 2021; Catanzaro et al, 2006; Cintra et al, 2017; Claudino et al, 2015; Cohen et al, 1963; Delle Monache et al, 2021; Ferreira et al, 2018; Garber et al, 2009; Glickman & Shklar, 1954; Ilić et al, 2012; Inagaki et al, 2010; Lee et al, 2016; Leite et al, 2008; Leite et al, 2010; Madani et al, 2014; Milosavljević et al, 2018; Müller et al, 2015; Nakajima et al, 2014; Santamaria‐Jr et al, 2021; Sugiyama et al, 2021; Uzunoglu‐Ozyurek et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…For the in vitro category, two studies performed a cell viability assay on human dental pulp cells (hDPCs) from extracted third molars of normoglycaemic and hyperglycaemic patients (Milosavljević et al, 2018; Uzunoglu‐Ozyurek et al, 2022), whereas other four used monolayer cultures of hDPCs (Müller et al, 2015; Nakajima et al, 2014) or rat dental pulp stem cells (RDSCs) (Sugiyama et al, 2021) incubated with or without advanced glycation end products (AGEs), or exposed to methylglyoxal (MG) (Delle Monache et al, 2021). Additionally, one article performed a mineralization assessment using cultured rat dental pulp cells (RPC‐C2A) incubated with or without different levels of glucose (10, 25 and 50 mmol/L) for up to 28 days (Inagaki et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein glycation and AGEs are well recognized in the development and pathogenesis of T2D complications however understanding the effect of hyperglycaemia on glycation in the human dental pulp is developing with most current knowledge being derived from animal studies (Miura et al, 2014; Nakajima et al, 2015; Sugiyama et al, 2022). In pulpitis, RAGE plays an important role in the immune response to bacteria and the expression of RAGE is upregulated in odontoblasts, stromal pulp fibroblasts and endothelial in response to infection (Tancharoen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Calcifications within the pulp are a known complication of T2D and they are also commonly seen on patient radiographs with increasing age (Inagaki et al, 2010; Maeda, 2020). A recent in vitro study using healthy dental pulp cells cultured from rats identified that AGE/RAGE signalling can induce calcification and cytotoxicity (Sugiyama et al, 2022) suggesting that in vivo this may result in abnormal tissue homeostasis. Furthermore, this response has the potential to be exacerbated in the hyperglycaemic tissue environment.…”
Section: Discussionmentioning
confidence: 99%